INVESTIGATING THE ENGLISH LANGUAGE NEEDS OF PURCHASING DEPARTMENT EMPLOYEES: A STUDY OF EOP - Multazam Abubakar; Muthi'ah Muthi'ah; Muhammad Syahruddin Nawir (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2021)
This paper aimed at investigating the needs of occupational English for Purchasing Department in PT. Bosowa Lloyd, Makassar. The subject of this research was 12 employees working in Purchasing Department consisting 6 males and 8 females, including one head which is called Purchasing Manager. The data were collected through a questionnaire, interview, and observation. The findings of this research indicates that Purchasing Department are required to have high levels of English proficiency. In order to prepare language program, the information of PSA becomes the starting point to design course and instruction material for the students. To identify TSA, the needs analysis for employee of Purchasing Department was performed through analyzing the responsibilities which were taken from company manual. Moreover, to meet the demands, communicative functioning (which covers discourse communities, business genre, key communication events and function, grammar and lexis), specific expectation of the students and the role of cross-cultural communication are also important to explore.